2017
DOI: 10.12669/pjms.331.12352
|View full text |Cite
|
Sign up to set email alerts
|

Initial results of efficacy and safety of Sofosbuviramong Pakistani Population: A real life trial Hepatitis Eradication Accuracy Trial of Sofosbuvir (HEATS)

Abstract: Objective:The uridine nucleotide analogue sofosbuvir is a selective inhibitor of hepatitis C virus (HCV) NS5B polymerase approved for the treatment of chronic HCV infection with genotypes 1 – 4. The objective of the study was to evaluate the interim results of efficacy and safety of regimens containing Sofosbuvir (Zoval) among Pakistani population with the rapid virologic response (RVR2/4 weeks) with HCV infections.Methods:This is a multicenter open label prospective observational study. Patients suffering fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…We previously reported an SVR (24 weeks) rate of 64% in patients treated with peginterferon and ribavirin in combination . In this present study, overall SVR12 was 95.9% (470/490), which is similar to those reported previously from other studies performed in the Indian subcontinent . Prior multicenter studies evaluating the efficacy of branded DAA have reported similar high SVR12 rates .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We previously reported an SVR (24 weeks) rate of 64% in patients treated with peginterferon and ribavirin in combination . In this present study, overall SVR12 was 95.9% (470/490), which is similar to those reported previously from other studies performed in the Indian subcontinent . Prior multicenter studies evaluating the efficacy of branded DAA have reported similar high SVR12 rates .…”
Section: Discussionsupporting
confidence: 91%
“…15 In this present study, overall SVR12 was 95.9% (470/490), which is similar to those reported previously from other studies performed in the Indian subcontinent. [16][17][18] Prior multicenter studies evaluating the efficacy of branded DAA have reported similar high SVR12 rates. [5][6][7]19 Our study supports the fact that generic DAAs are associated with high efficacy.…”
Section: Adverse Eventsmentioning
confidence: 95%
“…Another large multicenter study HEATS has found 98.2% patients achieving RVR in HCV infected patients with well tolerability. 28 The results of our study have found sofosbuvir to achieve 100% results of RVR and ETR in patients whose results have been collected and also SVR of patients chased also found 100% in both patients treated with dual and triple therapy.…”
Section: Discussionmentioning
confidence: 50%
“…Keeping in mind this important aspect of therapy success and future prediction, the current study was designed to analyse the available data regarding the HCV treatment with sofosbuvir from Pakistan. Literature survey showed that there are only 07 studies reporting the antiviral response of sofosbuvir in Pakistan [12][13][14][15][16][17][18] . The available limited data showed that overall sustained virological response (SVR)/rapid virological response (RVR) is very good.…”
Section: Gastroenterology and Hepatology Researchmentioning
confidence: 99%
“…Capileno et al (2017) study from Karachi included 153 patients and reported that 84% patients showed RVR [13] . The detailed analysis of available data suggested a very good response for this DAA antiviral regimen in different cities with overall 80-100% SVR/RVR [13][14][15][16][17][18] . There is also a study which included 37 renal transplant HCV patients from Karachi and sofosbuvir treatment showed 89.2% RVR for these individuals [19] .…”
Section: Gastroenterology and Hepatology Researchmentioning
confidence: 99%